Comparison of analgesic efficacy of dexamethasone as an adjuvant to bupivacaine using ultrasound-guided caudal block in children undergoing infraumbilical surgeries - Randeep Kaur; Ruchi Gupta; Gaganjot Kaur (The Indian Anaesthetists' Forum)
Background and Aims: Regional anesthesia is most effective in obtunding surgical stress and has become a routine intervention in children and infants. Caudal analgesia using local anesthetics is a traditionally used technique, but provides a limited duration of analgesia. Several adjuvants can be added to local anesthetics to increase the duration of action. This study was undertaken to evaluate the analgesic efficacy of dexamethasone added to bupivacaine for caudal block in children. Materials and Methods: This was a prospective, double-blinded study done on 70 children of age group 1–7 years allocated randomly into two groups. Children in Group C received 1 mL/kg of 0.25% bupivacaine alone and in Group D received 1 mL/kg of 0.25% bupivacaine along with 0.1 mg/kg dexamethasone under ultrasound guidance planned for infraumbilical surgeries. The primary outcome of our study was postoperative duration of analgesia. The secondary outcomes measured were number of rescue doses, caudal effective score, and complications. Results: The mean duration of analgesia when dexamethasone was added to caudal bupivacaine was 416.91 ± 110.89 min, while in Group C, it was 297.88 ± 85.43 min. The number of doses of rescue analgesics doses required and the incidence of nausea and vomiting were also lesser in Group D. Conclusion: Addition of 0.1 mg/kg of dexamethasone to caudal bupivacaine (0.25% of 1 mL/kg) significantly improves analgesic efficacy and decreases the requirement of rescue analgesia as well as antiemetics.